2021
DOI: 10.1029/2021gl094638
|View full text |Cite
|
Sign up to set email alerts
|

Formation of East Asian Stagnant Slabs Due To a Pressure‐Driven Cenozoic Mantle Wind Following Mesozoic Subduction

Abstract: The term "stagnant slab" usually refers to the widely distributed fast seismic anomalies within the circum-Pacific mantle transition zones (MTZ) (Fukao et al., 2009;Huang & Zhao, 2006). There are several proposed mechanisms for why slabs can stagnate in the MTZ. The first one is related to the buoyancy associated with phase transformations of major mantle minerals, where both the negative Clapeyron slope of the ringwoodite-bridgmanite transformation (Christensen & Yuen, 1985;Tackley et al., 1993) and the delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…In this study, we perform global mantle convection models to examine the behaviors of the Izanagi plate and the Pacific plate since the Mesozoic time. We introduce a tracking procedure in numerical models to explicitly distinguish the slab materials of the two plates, which provides a more robust demonstration of slab dynamics in their evolutionary processes than identifying slabs solely from thermal structures as in many previous studies (e.g., Seton et al, 2015;Peng et al, 2021a;. Our results show a general match of present-day slab structures beneath Eastern Asia with those inferred from seismic tomography observations, especially in the upper-to-middle mantle depths.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this study, we perform global mantle convection models to examine the behaviors of the Izanagi plate and the Pacific plate since the Mesozoic time. We introduce a tracking procedure in numerical models to explicitly distinguish the slab materials of the two plates, which provides a more robust demonstration of slab dynamics in their evolutionary processes than identifying slabs solely from thermal structures as in many previous studies (e.g., Seton et al, 2015;Peng et al, 2021a;. Our results show a general match of present-day slab structures beneath Eastern Asia with those inferred from seismic tomography observations, especially in the upper-to-middle mantle depths.…”
Section: Discussionsupporting
confidence: 58%
“…Although some regional models have suggested that the weak layer has a small effect on slab stagnation (e.g., , global models have demonstrated that the weak layer is crucial to explain not only the stagnant slabs in the transition zone (e.g., East Asia) but also other slab structures (e.g., North America) that are observed in seismic tomography studies (Mao and Zhong, 2018). Recent numerical studies, on the other hand, have argued that a pressure-driven Cenozoic mantle wind is the dominant mechanism for the formation of the stagnant slabs beneath East Asia (Peng et al, 2021a). The linkage between the Izanagi plate subduction and the tectonic evolution of East Asia is still controversial because the slab dynamics of the Izanagi plate have not been well resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the subduction of the Izanagi-Pacific ridge, however, hot material may then have flowed through the opened slab window into East Asia, and been driven further into this region by downwelling slabs during the Cenozoic. Indeed, this east-west Poiseuille flow following the subduction of the Izanagi-Pacific ridge has recently been noted, and invoked as a cause of the flat-slab subduction style of the Pacific plate (Peng et al, 2021).…”
Section: Introductionmentioning
confidence: 92%
“…In contrast to the general northwestward subduction of the PSP, our imaged lower mantle slab presents a SE-dipping structure (Figure 10b), which suggests complicated mantle dynamics in the lower mantle. The recent global-scale dynamic models of Peng et al (2021) show examples with the lower-mantle portion of the subducted Pacific slab displaying an eastward-dipping direction from the shallower slab, due to a westward mantle flow going through the slab gap in between them. Alternatively, a slab avalanche into the lower mantle can produce a complicated slab morphology in the lower mantle with a possible reversed dipping direction (Agrusta et al, 2017;Goes et al, 2008Goes et al, , 2017Nakakuki et al, 2010;Yang et al, 2018).…”
Section: Implication Of Plate Tectonicsmentioning
confidence: 99%